Plio-Pleistocene time-averaged field in southern Patagonia recorded in lava flows - Mejia, V.; Opdyke, N. D.; Vilas, Juan Francisco A.; Singer, B. S.; Stoner, J. S. (Geochemistry, Geophysics, Geosystems)
Paleomagnetic directions were obtained from stepwise alternating-field or thermal demagnetization of 53 lava flows from southern Patagonia (latitudes 49.5°-52.1 °S) that include the Pali-Aike volcanic field and the Meseta Viscachas plateau lavas. In addition to previous Miocene-late Quaternary ages of these flows, 40Ar/39Ar dates spanning from 0.1 to 15.4 Ma were obtained for 17 of the sites. All except one of the magnetic polarities coincide with the expected polarities of the magnetic polarity timescale [Cande and Kent, 1995] for the obtained 40Ar/39Ar ages. The mean direction from 33 sites (eliminating sites <4 Ma) that pass a selection criteria of α95 ≤5° is Dec = 358.7°,Inc = - 68.2°, α95 = 3.5°, a value that coincides within the statistical uncertainty with the direction of the geocentric axial dipole for that area (Inc = - 68.1°). Likewise, the mean virtual geomagnetic pole (VGP) coincides within the statistical uncertainty with the geographic North Pole. The secular variation described by the VGP angular standard deviation for these sites is 17.1°, a value expected for that latitude according to Model G of paleosecular variation [McFadden et al., 1988]. The characteristics of the data presented are optimum for time-averaged field (TAF) studies because of the good age control and good quality of the paleomagnetic data: (1) primary components of magnetization were obtained using principal component analysis [Kirschvink, 1980] from at least five points and maximum angular deviation ≤5°, (2) site means were calculated with Fisher statistics using at least three samples, and (c) 38 of the 53 flows had α95 ≤ 5°. No results (five sites) or high α95 values (≤5°) were obtained primarily from sites affected by lightning. Fil: Mejia, V. University of Florida; Estados Unidos Fil: Opdyke, N. D. University of Florida; Estados Unidos Fil: Vilas, Juan Francisco A. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Geología; Argentina. Consejo Nacional de Investigaciones ...